ENGLISH REMOVAL FOR ELEMENTARY SCHOOL IN 2013 CURRICULUM; A CARELESS OR CAREFUL STEP? - Yulian Purnama (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
The idea of removing English for elementary school in 2013 curriculum has shocked the Indonesian education practitioners. So far, English has been considered as a favorite and prestigious subject for some modern elementary schools. English lessons is claimed to be important and is still needed by the young learn-ers. Given the context of EFL (English as a Foreign Language) teaching English in Indonesia, of course, may not equate with the teaching of English in Singapore where English is in the context of ESL (English as a Second Language). As the right method and strategy may be given to the learners, the development of lan-guage skills for children aged 6-12 years-old will not be disturbed. Then if the mother tongue, that is Bahasa Indonesia, would not be a mess if at the same time the students need to learn a foreign language. In the end, learning English will not lose identity or sense of nationalism of the students. Keywords: Young learners, English, 2013 Curriculum